Азықлылық цехлары ушын от-шөп майдалағышларды таңлаў - Султанов, Е.К; Рамазанов, Б.Н; Жумамуратова, В.Б; Қарлыбаев, А.М (SCIENCE and SOCIETY, 2022)
The article provides recommendations for the ISK-3A reed grinder-mixer in the feed preparation shops of dairy farms in the Republiс
Keywords: meat and dairy products; technological process; ration; fodder shops; stationary and mobile; mixer grinder ISK-3A